HUBUNGAN PENINGKATAN KADAR CREACTIVE PROTEIN DENGAN PENURUNAN FUNGSI KOGNITIF PASIEN GERIATRI RAWAT JALAN - Stefanus Erdana Putra,* Muhammad Hafizhan,** Raden Ajeng Hanindia Riani Prabaningtyas* (NEURONA, 2019)
INTRODUCTION GERIATRIC PATIENTS HAVE DIFFERENT CHARACTERISTICS COMPARED TO OTHER PATIENTS IN GENERAL IN WHICH THEY POTENTIALLY EXPERIENCING COGNITIVE IMPAIRMENT DECREASING OF PHYSIOLOGICAL AND FUNCTIONAL STATUS ALSO THE IMMUNOLOGICAL SYSTEM THIS SITUATION CAUSES VARIOUS INFLAMMATORY REACTIONS THAT PLAY A ROLE IN THE DEVELOPMENT OF NEURODEGENERATIVE DISEASES INCLUDING THE INCREASE PRODUCTION OF ACUTE PHASE PROTEIN CALLED CREACTIVE PROTEIN CRP